Endovascular Treatment of a Right-Sided Ureteroiliac Fistula in a Patient with a Simultaneous Left-Sided Ureteroileal Fistula - G. M. Veenstra; L. M. C. L. Fossion; G. Debonnaire; K. de Laet (Case Reports in Urology)
We describe an 80-year-old female with a left ureteroileal fistula and simultaneously a right ureteroiliac fistula. Her history highlights the predisposing factors of radiation, major surgery in the region, and presence of bilateral double-J-stents. She was successfully treated with an endovascular approach after being initially misdiagnosed. There seems to be an increase in reporting ureteral fistulas, however this entity remains a rare clinical condition that can lead to life-threatening situations. A fast and accurate diagnosis of an ureteroarterial fistula remains a challenge.